Etika Konsumsi Dalam Ekonomi Islam - Mirahandani M; M Raihan; Rizqa Amelia (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Â The Islamic study of consumption is essential if one is to restrain oneself with possessions and expenses. makes a country have a lot of money, welfare will not work if it is not used wisely and the benefits are not measurable. The best approach to using one's wealth for the betterment of oneself, one's community, and people as a whole is to direct one's preferences towards options that contain maslahah (good and beneficial). The drive to satisfy one's basic needs is innate in the human condition. Especially babies, humans always find ways to communicate their desires to meet their needs, such as babies screaming for milk when they are hungry. As we grow older and more capable, our wants and needs peak as we reach puberty and gradually decline until death.